Comparison of synchronization between left bundle branch and his bundle pacing in atrial fibrillation patients: An intra‐patient‐controlled study. Issue 9 (24th August 2021) - Sheng, Xia; Pan, Yi‐Wen; Yu, Chan; Wang, Bei; Zhang, Pei; Li, Jing; Zhang, Jie‐Fang; Chen, Shi‐Quan; Wang, Min; Sun, Ya‐Xun; Jiang, Dong‐Mei; Yang, Ying; et al.
Abstract: Background: His bundle pacing (HBP) is a physiological pacing strategy to preserve the electrical synchrony of ventricular conduction and left ventricular (LV) function. Left bundle branch pacing (LBBP) has emerged as an alternative physiological pacing technique. Objective: To evaluate cardiac electrical and mechanical synchrony comparing LBBP and HBP in patients with permanent atrial fibrillation (AF). Methods: Consecutive patients with symptomatic bradycardia and AF were enrolled from January to June of 2019. The cardiac electrical and mechanical synchrony in different pacing mode were evaluated at baseline and after implantation. Results: Both HBP and LBBP were performed in 20 patients. LBBP significantly widened the QRS duration compared with the intrinsic conduction (113.2 ± 14.5 vs. 96.5 ± 16.2 ms; p = .01), while HBP did not (104.5 ± 22.3 vs. 96.5 ± 16.2 ms; p = .12). Both LBBP and HBP patients had similar LV myocardial strain measurements for the mechanical synchrony evaluation without significant change compared with baseline. There was no significant difference in right ventricular synchrony measurement between LBBP and HBP. Compared to HBP, LBBP had less interventricular synchrony (IMVD, 14.7 ± 9.2 vs. 3.1 ± 12.7 ms, p < .01; Ts‐LV‐RV, 37.9 ± 10.7 vs. 18.5 ± 10.8 ms, p < .001). Conclusions: Although LBBP's a physiological pacing mode can achieve a similar cardiac electrical and mechanical synchronization when compared to HBP, LBBP results in modest delay in RV activation, and the clinical implication remains to be studied.